2019
DOI: 10.3390/rs11242956
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Grassland Degradation in Zona da Mata, MG, Brazil, Based on NDVI Time Series Data with the Integration of Phenological Metrics

Abstract: There is currently a lot of interest in determining the state of Brazilian grasslands. Governmental actions and programs have recently been implemented for grassland recovery in Brazilian states, with the aim of improving production systems and socioeconomic indicators. The aim of this study is to evaluate the vegetative growth, temporal vigor, and long-term scenarios for the grasslands in Zona da Mata, Minas Gerais State, Brazil, by integrating phenological metrics. We used metrics derived from the normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
(71 reference statements)
0
20
0
1
Order By: Relevance
“…It is widely used in hydrology, climate, and other fields [14][15][16]. Previous studies have shown that the Hurst exponent based on the rescaled range (R/S) is more stable than other methods [17]. Therefore, we selected the Hurst exponent to analyse the continuity in NDVI trends from 2000 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely used in hydrology, climate, and other fields [14][15][16]. Previous studies have shown that the Hurst exponent based on the rescaled range (R/S) is more stable than other methods [17]. Therefore, we selected the Hurst exponent to analyse the continuity in NDVI trends from 2000 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the Hurst exponent based on the rescaled range (R/S) is more stable than other methods [17]. Therefore, we select the Hurst exponent to analyze the NDVI trend's continuity from 2000 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Vegetation indices, especially the Normalized Difference Vegetation Index (NDVI), have been usually used for the generation of phenological metrics. Traditionally the moderate resolution imaging spectroradiometer (MODIS) and advanced very high-resolution radiometer (AVHRR) products were widely used to estimate the phenological metrics [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%